PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE GUNA MENINGKATKAN AKTIVITAS BELAJAR PKN SISWA KELAS V SDN 219 MUARA SIAMBAK - Muhammad Taon (Universitas Negeri Medan, 2017)
Abstract: Implementation of Think Talk Write Learning Model to Increase Student Learning Activity of Grade V SDN 219 Muara Siambak. This study aims to improve learning outcomes and improve student learning activities in class V on Civics subjects with TTW (Think-Talk-Write) SDN 219 Muara Siambak learning model. The subjects of this study are all students of grade V SDN 219 Muara Siambak with the number of students 24 people. Activity learning cycle I with 2 meetings, and learning cycle II with 2 meetings. The end of KBM cycle I and the second cycle of KBM conducted test results Formative Form I and Form II results respectively show 69.17 and 85.83 with the percentage of classical completeness is 58.33% and 91.67%. Seeing the data there are changes and changes are due to teacher actions during KBM in Cycle I and cycle II.Keywords: TTW, learning outcomes, learning activitiesAbstrak: Penerapan Model Pembelajaran Think Talk Write Guna Meningkatkan Aktivitas Belajar Pkn Siswa Kelas V SDN 219 Muara Siambak. Penelitian ini bertujuan untuk meningkatkan hasil belajar dan meningkatkan aktivitas belajar siswa dikelas V pada mata pelajaran PKn dengan model pembelajaran TTW (Think-Talk-Write) SDN 219 Muara Siambak. Subjek penelitian ini adalah seluruh siswa kelas V SDN 219 Muara Siambak dengan jumlah siswa 24 orang. Kegiatan pembelajaran siklus I dengan 2 kali pertemuan, dan pembelajaran siklus II dengan 2 kali pertemuan. Akhir KBM siklus I dan KBM siklus II dilakukan tes hasil belajar Formatif I dan Formatif II hasilnya masing-masing menunjukkan 69.17 dan 85.83 dengan persentase ketuntasan klasikal adalah 58.33% dan 91.67%. Melihat data tersebut ada perubahan dan perubahan tersebut akibat tindakan guru selama KBM pada Siklus I dan siklus II.Kata kunci : TTW, hasil belajar, aktivitas belajar